Outcomes of surgical repair of a single digital nerve in adults - Jain, A; Dunlop, R; Hems, T; Tang, JB (SAGE Publications, 2019)
Current standard management of a cut digital nerve is end-to-end microsurgical nerve coaptation where possible. A recent systematic review of adult digital nerve injuries that were either repaired or left unrepaired showed that the evidence for good nerve recovery or improved function following nerve repair is poor. In the 30 studies included, only 24% of repaired nerves regained sensory recovery close to or equivalent to estimated pre-injury levels. Neuroma rates were the same in those nerves repaired (4.6%) and those not repaired (5%). Questions under debate include proper assessment methods of outcomes, decision making for repair or no repair to different fingers or the thumb, levels of injury, age, and hand dominance. This review summarizes the major evidence available and debates the surgical dogma that surrounds this injury.